The Relationship Of The Value Of Monthly Pay Money To The Motivation Of Learning Fikh On Santri Al-Hidayah Islamic Boarding School Purwakarta - Imam Tabroni, (International Journal of Social Science, 2022)
This study aims to describe and how the correlation between monthly pocket money and students' learning motivation at Al-Hidayah Islamic Boarding School. This is important to study considering how far the influence of the monthly allowance of santri given by parents to meet their daily needs in a month.The method used in this study is quantitative correlation and data analysis using descriptive statistics. The sampling technique was carried out by random samples. The data collection technique was carried out using a Likert scale questionnaire technique. While quantitative analysis using descriptive analysis, prerequisite analysis test, analysis of hypothesis testing, correlation and regression analysis using software assistance